Pengaruh Pertumbuhan Jumlah Penduduk Dan Produk Domestic Regional Bruto Terhadap Indeks Pembangunan Manusia Di Pulau Sumatera Tahun 2015-024 Dalam Perspektif Ekonomi Islam - Ningsih, Dwi Arya; Fatih Fuadi; Is Susanto (Li Falah: Journal of Islamic Economics and Business, 2026)
This study aims to examine, from an Islamic economics perspective, the effects of population growth and Gross Regional Domestic Product (GRDP) on the Human Development Index (HDI) across Sumatra Island during the 2015–2024 period. Using a quantitative approach, this research employs panel data obtained from the Central Statistics Agency (BPS) and analyzes the data through panel regression with the Fixed Effect Model (FEM). The results reveal that population growth has a positive and significant effect on HDI, while GRDP exerts a negative and significant effect; furthermore, both variables simultaneously influence HDI significantly. The coefficient of determination (R²) indicates that the independent variables explain a substantial proportion of the variation in HDI across the observed provinces. From the perspective of Islamic economics, these findings suggest that human development is determined not only by economic growth but also by the quality of human resources and equitable distribution, emphasizing that the achievement of comprehensive welfare (falah) requires a balance between economic expansion and social justice.